CHALLENGES FACED BY MICRO AND SMALL BUSINESSES TO SURVIVE - Ria Satyarini; Meidila Anggita; Ignasia Tiffani; Triyana Iskandarsyah (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2025)
Micro and small business owners have to fight for their businesses to survive. In order to survive, micro and small business actors must first know the problems they face. The method used to find out the problems faced by conducting observations and also interviews with micro business actors. This research reveals the problems faced by micro and small business actors based on three company operating functions, namely Operations Management, Financial Management and Marketing Management. The results show that in the Operations section, micro and small business actors must improve production planning, 5S and layout arrangement. In the financial section, what must be addressed is financial recording, and in the marketing section, what must be addressed is product development and market expansion by penetrating the marketplace. Improvement of the problems faced is carried out by assisting MSEs by improving the company's operating functions